Contemporaneous Insufficiency Fractures of Bilateral Femoral Necks in an Older Patient Taking Bisphosphonate: A Case Report and Literature Review - Hiroaki Tagomori; Nobuhiro Kaku; Shota Sato; Tsuguaki Hosoyama; Hiroshi Tsumura (Case Reports in Orthopedics)
We report, to the best of our knowledge, the first case of simultaneous insufficiency fracture of the bilateral femoral neck in an older patient taking bisphosphonate. Femoral neck fractures frequently occur in older individuals because of traumatic incidents, such as a fall. A 74-year-old woman with osteoporosis was taking raloxifene hydrochloride and bisphosphonate for approximately 5 and 3 years, respectively. Despite no history of falls or any other traumatic incidence, the patient reported cooccurrence of pain on both sides of the hip. Imaging revealed bilateral femoral neck fractures. Bipolar hemiarthroplasty and internal fixation were conducted on the right and left hips, respectively. At 6 months postoperatively, the patient reported gradual disappearance of left hip pain, and a radiograph revealed that the fracture had healed. Overall, clinical and histological findings suggested an atypical fracture, thereby proving that this type of fracture can occur in areas other than the femoral shaft.